Book Review: UNIDROIT Principles of International Commercial Contracts – An Article-by-Article Commentary - Butler, Petra (Victoria University of Wellington Law Review, 2018)
Book review of Eckart J Brödermann UNIDROIT Principles of International Commercial Contracts: An Article-by-Article Commentary (Wolters Kluwer, Aalphen aan den Rijn, 2018).